Treating transsexuals in India: History, prerequisites for surgery and legal issues - Richie Gupta; Anil Murarka (Indian Journal of Plastic Surgery)
Authors in their clinical practice came across transsexual patients, who were determined to get their gender affirmed by undergoing a change of sex. This motivated the authors to review the literature extensively regarding transsexualism and report their experience. Opinions were taken from legal luminaries practicing in related fields. They also took inputs from several patients who were at various stages of psychiatric analysis and hormone therapy and also those, who had completed their treatment procedures. A paucity of the Indian inputs in medical literature concerning transsexualism was noted by the authors They also found deficiencies in the Indian Law, as applied to the individuals undergoing gender affirmation surgery (GAS). In this paper they have enumerated these deficiencies. Though GAS has been legally allowed in U.K. since 1967, in America since 1972, and in various other countries, Indian Laws are silent on the issue. An Indian surgeon dealing with transsexual patients is faced with a number of issues like consent for the procedure, safe guarding the surgeon or gender team from future litigation. Another issue is postoperative sexual and legal status of the patient. Present Indian Laws regarding marriage, adultery, sexual and unnatural offences, adoptions, maintenance, succession, labour and industrial laws will require modifications when dealing with these individuals and protecting their rights. Authors have tried to deal with all these issues that an individual surgeon faces when he manages a transsexual patient.